164k views
4 votes
Which equation has the same solution as x^2-6x-14=0

A: (x+3)^2=23
B: (x-3)^2=23
C: (x+3)^2=5
D: (x-3)^2=5

User Sena
by
5.9k points

2 Answers

3 votes
B. X^2-6x. =14
Half of -6 is -3 and -3^2=9 so add 9 to both sides
X^2-6x+9 = 14+9
(X-3)^2= 23
User Colas
by
6.2k points
1 vote

Answer:

(x-3)² = 23 Option B

Explanation:

Given quadratic is :

x² - 6x - 14 = 0

Use complete the square method

Move loose term from left side to right side.

x² - 6x = 14

add both the side square of half coefficient of x that is,

half of -6 = -3

square of -3 = 9

Add both the side 9

x² - 6x + 9 = 14 + 9

(x - 3)² = 23

this is same as (x-3)²=23 second option

That's the final answer.

User Peyman Gilmour
by
6.4k points